The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1968
DOI: 10.1002/1097-0142(196808)22:2<379::aid-cncr2820220215>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and histology of oral leukoplakia and leukoedema among papuans and New Guineans

Abstract: The prevalence of leukoedema, preleukoplakia and leukoplakia has been studied among 1226 Papuans and New Guineans in two coastal areas and in one highland area. Leukoedema is found in 2.4‐16.9%, preleukoplakia in 10.6‐ 13.4% and leukoplakia in 3.1‐6.2%. Chewing and smoking habits seem to be associated with varying rates of the conditions recorded. In view of a previously supposed obvious association with the betel chewing habit, it is deeply interesting that the results of this study indicate that smoking may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1
2

Year Published

1969
1969
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 2 publications
3
47
1
2
Order By: Relevance
“…However, it is of interest to note that when the superficial parts of the keratin layer is invaded by microorganisms, as in chronic hypertrophic candidosis, the state of keratinization seen is always parakeratosis (Cawson and Lehner, 1968). Pindborg et al (1964) and Meyer et al (1967) have shown that the oral epithelium in different sites of the oral cavity show a great variation in reaction to the different oral habits, and great variability exists even in the reactions of the epithelium of a single site to the same habit. Thus, Pindborg et al (1964) found that hyperorthokeratosis was the most common hypercornification in the cheek mucosa of Indians following betel-nut chewing with tobacco.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is of interest to note that when the superficial parts of the keratin layer is invaded by microorganisms, as in chronic hypertrophic candidosis, the state of keratinization seen is always parakeratosis (Cawson and Lehner, 1968). Pindborg et al (1964) and Meyer et al (1967) have shown that the oral epithelium in different sites of the oral cavity show a great variation in reaction to the different oral habits, and great variability exists even in the reactions of the epithelium of a single site to the same habit. Thus, Pindborg et al (1964) found that hyperorthokeratosis was the most common hypercornification in the cheek mucosa of Indians following betel-nut chewing with tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Pindborg et al (1964) and Meyer et al (1967) have shown that the oral epithelium in different sites of the oral cavity show a great variation in reaction to the different oral habits, and great variability exists even in the reactions of the epithelium of a single site to the same habit. Thus, Pindborg et al (1964) found that hyperorthokeratosis was the most common hypercornification in the cheek mucosa of Indians following betel-nut chewing with tobacco. Sirsat and Doctor (1967) stated that parakeratosis was a common finding while hyperkeratosis was less commonly observed, whilst Meyer et al (1967) found that no specimen was wholly ortho-or wholly parakeratinized, but that orthokeratotic, parakeratotic and unkeratinized regions were combined in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is of interest to note that Chang (1966) observed discernible clinical changes in the oral mucosa in 56 out of 174 betel-nut chewers (32X1 %) in Taiwan who do not use tobacco but use a shell-lime and betel-nut mixture. Pindborg, Barmes and Roed-Peterson (1968) studied the prevalence of leukoedema, preleukoplakia and leukoplakia among Papuans and New Guineans. In the North Coast Area where 95% of the study sample examined were betel-nut chewers (non-tobacco) 62 out of 283 Slight chewers Loss than 10 years' history of habit and "intensity of habit " less than one hour per day.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in composition of the quid Pindborg, Kiaer, Gupta and Chawla (1967) reported 38 different habitual ways in which tobacco and/or betel-nut were used, and it is necessary therefore to categorize the method of usage, before comparative studies can be made. All subjects in the present series chewed betel-nut in the form of a quid or " pan ".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation